A COMPARATIVE STUDY OF NUTRIENT TRANSFER VIA SURFACE RUNOFF FROM TWO SMALL AGRICULTURAL CATCHMENTS IN NORTH CHINA - Lu H.; Yin Ch.; Wang W.; Shan B. (My University, 2007)
A field study was conducted to determine the effect of landscape spatial pattern and micro-topography on nutrient transfer via runoff from two catchments into Yuqiao Reservoir in north China. The surface runoff discharge was measured during rainfall events and water samples were analyzed in 2004 and 2005. The mean annual total nitrogen (TN) and total phosphorus (TP) exports per unit area from Caogezhuang catchment (C catchment) were 1.048 and 0.561 kg ha−1 year−1, respectively, while the TN and TP exports from Taohuasi catchment (T catchment) were 0.158 and 0.027 kg ha−1 year−1. In both catchments, village and vineyard shared the highest nutrient export ability due to the accumulated animal waste and heavy application of fertilizer and manure. In T catchment, the distance of village and vineyard was about 1,500 m away from the receiving water and in between were woodland and cropland. In the hydrological pathway, there were sink landscape structures of small stone dams, roadside swale, vegetated filter strip and dry ponds, which could detain water and nutrients. In C catchment, the distance between the village and the receiving water was about 200 m, and the hydrological pathway was compacted roads and ditches with no sink structures. It is suggested that the distance between the pollution source area and the receiving water and the micro-topographical features were the main factors to control the great difference in nutrient export rates.
Keywords: AGRICULTURAL CATCHMENT; LANDSCAPE SPATIAL PATTERN; MICROTOPOGRAPHY; NUTRIENT TRANSFER; SURFACE RUNOFF